LEGAL PROTECTION FOR CONSUMERS WHO EXPERIENCE LOSSES DUE TO SELLING GOLD JEWELRY IN DIFFERENT STORES - Zhafira Ramadhani; Noor Fatimah Mediawati (International Journal of Business, Law and Political Science, 2025)
Objective: This study aims to analyze the factors affecting the differences in selling prices of gold jewelry in different shops from the original purchase location. Gold is often chosen as an investment vehicle by the public due to its stable resale value. However, the variation in resale prices of gold jewelry across various shops presents a challenge for consumers. Method: This research employs a normative method with a statutory approach and descriptive analysis technique with deductive conclusions. The data used includes primary data in the form of relevant laws and regulations as well as secondary data from books and journals. Results: The findings reveal that the differences in the selling prices of gold jewelry are influenced by several factors, including individual store pricing policies, production costs, the condition of the jewelry, and fluctuations in gold market prices. Novelty: This study is expected to provide better understanding for consumers in making decisions when selling gold jewelry and to benefit the government, industry players, academics, and society in developing the gold industry in Indonesia.